Fala, escrita e outras expressões de uma criança com autismo: aspectos da constituição subjetiva - Fonseca, Pauline Luise Von Brusky Sales da (2020)
This work focuses on language and subjectivity in autism, from the conception of psychoanalysis of French origin, presenting a clinical case of a child with the initial medical diagnosis of autism. The foundation that guides this dissertation is the premise of Jacques Lacan for whom the unconscious is structured as a language. The research method adopted is the clinical case study, which seeks to understand the value of speech and writing for a child, from the 3 years old, accompanied in individual sessions of one hour, once a week and, presents clinical interventions that resulted from his peculiar movement. It distinguishes between enunciative speech and a mere apprehension of language by memorizing a glossary of words, which is not addressed, does not allow dialogue, does not carry a message. It addresses the subjective constitution in the autism clinic. Considers that children with autism can access speech and writing, through psychic operations that insert them, in the symbolic field